2016
DOI: 10.3390/v8010026
|View full text |Cite
|
Sign up to set email alerts
|

Branched Lateral Tail Fiber Organization in T5-Like Bacteriophages DT57C and DT571/2 is Revealed by Genetic and Functional Analysis

Abstract: The T5-like siphoviruses DT57C and DT571/2, isolated from horse feces, are very closely related to each other, and most of their structural proteins are also nearly identical to T5 phage. Their LTFs (L-shaped tail fibers), however, are composed of two proteins, LtfA and LtfB, instead of the single Ltf of bacteriophage T5. In silico and mutant analysis suggests a possible branched structure of DT57C and DT571/2 LTFs, where the LtfB protein is connected to the phage tail via the LtfA protein and with both protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 50 publications
9
50
0
Order By: Relevance
“…The gene encoding MAR003J3_00081 is an orthologue of ltfA in phage DT57C and DT571/2 which with l tfB encode for L‐shaped tail fibres that allow attachment to different O‐antigen types. This arrangement of two genes encoding the L‐shaped tail fibres is different from T5, which encodes the L‐shaped tail fibres in a single gene (Golomidova et al, ; Nobrega et al, ). vB_Eco_mar003J3 contains orthologues of both ltfA and ltfB , suggesting that it too uses two gene products for L‐shaped tail fibres, whereas vB_Eco_mar004NP2 only contains an orthologue of ltfB (MAR004NP2_00162) and does not contain an orthologue of the single gene used by T5 ( ltf ).…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding MAR003J3_00081 is an orthologue of ltfA in phage DT57C and DT571/2 which with l tfB encode for L‐shaped tail fibres that allow attachment to different O‐antigen types. This arrangement of two genes encoding the L‐shaped tail fibres is different from T5, which encodes the L‐shaped tail fibres in a single gene (Golomidova et al, ; Nobrega et al, ). vB_Eco_mar003J3 contains orthologues of both ltfA and ltfB , suggesting that it too uses two gene products for L‐shaped tail fibres, whereas vB_Eco_mar004NP2 only contains an orthologue of ltfB (MAR004NP2_00162) and does not contain an orthologue of the single gene used by T5 ( ltf ).…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli lytic myovirus phi92 has at least five different tail spikes and tail fiber proteins identified by cryoelectron microscopy, allowing it to infect a wide range of E. coli and Salmonella strains (54). Two different RBPs, LtfA and LtfB of the T5-like siphoviruses DT57C and DT571/2, recognize different O antigens, i.e., the O22 or O87 type and the O81 type, respectively (55). Two different carbohydrate-binding modules have been identified in Lactococcus lactis phage Tuc2009; the first is in a classical bona fide RBP (BppL), and the other is in an accessory protein, BppA (56).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that the presence of acetyl groups on the O-antigen protects E. coli 4s from infection of certain T5-like bacteriophages. These viruses (e.g., DT571/2 and fibreless mutants of phage DT57C) possess long non-contractile tails and recognize membrane proteins, but not LPS, on the cell surface (Golomidova et al, 2016). They cannot infect WT 4s but grow well on E. coli 4sI or 4sR that carry a non-acetylated O-antigen or no O-antigen at all (Golomidova et al, 2016).…”
Section: G7c Alters Non-specific Phage Defense Of the Hostmentioning
confidence: 99%
“…These viruses (e.g., DT571/2 and fibreless mutants of phage DT57C) possess long non-contractile tails and recognize membrane proteins, but not LPS, on the cell surface (Golomidova et al, 2016). They cannot infect WT 4s but grow well on E. coli 4sI or 4sR that carry a non-acetylated O-antigen or no O-antigen at all (Golomidova et al, 2016). The mechanism of this effect is unclear, but one can speculate that the O-acetyl groups enhance the interaction between the neighboring O-antigen chains thus creating a less penetrable surface layer.…”
Section: G7c Alters Non-specific Phage Defense Of the Hostmentioning
confidence: 99%